STABILITY OF TOMATO (SOLANUM LYCOPERSICUM [L.]) FRUIT WEIGHT AND DIRECT AND INDIRECT CONTRIBUTION OF AGRONOMIC TRAITS UNDER POLYHOUSE CONDITION IN SUDAN AGRO-ECOLOGY - Adeniji, O. T.; Jandong, E.A.; Ahmad, I.; Adekoya, M.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was carried out to understand phenotypic variability and stability concerning fruit weight and quality, as well as the contribution of various traits to fruit weight per plot under polyhouse conditions in Sudan agroecology during the 2019-20 growing season. Six tomato cultivars were cultivated in a randomized block design (RBD) with four replicates in a polyhouse. Data collected include phenological, morpho-physiological, fruit weight per plot, and quality traits. The findings indicated significant variability in both fruit weight and quality traits. Notably, the days to appearance of first fruit and mature fruit, as well as fruit height and width, total soluble solids (TSS), and fruit weight per plot were affected by the interaction between hybrid and microclimatic factors. The varieties 'TSU02’, ‘TSU03' and ‘TSU05’ demonstrated phenotypic insensitivity to these microclimatic factors, exhibiting moderately high fruit weight per plot. Furthermore, 'TSU04', 'TSU02’ and ‘TSU03’ displayed stable performance for TSS across the years. The contribution of fruit weight and number of fruits per plant were significant in determining overall fruit yield, while individual fruit weight served as a valuable index for fruit yield improvement. The relationship between fruit weight per plot and indirect effects of fruit length and fruit per infructescence indicates a compromise in developing high-yielding varieties. Thus 'TSU02’ and ‘TSU03’ emerged as a promising hybrid for enhancing fruit weight and total soluble solids in polyhouse cultivation within Sudan agroecology.